2014
DOI: 10.3233/npm-14814014
|View full text |Cite
|
Sign up to set email alerts
|

Serum apelin in early-onset neonatal sepsis: Is it diagnostic?

Abstract: OBJECTIVE: To evaluate the diagnostic value of serum apelin in early-onset neonatal sepsis in full term neonates. Apelin is a proinflammatory adipocyte-derived factor that participates in vascular wall inflammation. STUDY DESIGN: Case-control study was conducted on 60 full term neonates, 30 cases with early-onset neonatal sepsis and 30 healthy matched controls. Complete blood counts, C-reactive protein, blood cultures, plasma lactate, and serum apelin concentrations (measured by enzyme-linked immunosorbent ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
2
5
0
2
Order By: Relevance
“…This study illustrated that there was an increase in the level of serum apelin in the sepsis group compared to the non-sepsis group. Gad et al 14 found an 8-fold increase of serum apelin in neonates with sepsis compared to the controls. Apelin is upregulated following sepsis, and plays a protective role in sepsis-induced cardiac impairment.…”
Section: Discussionmentioning
confidence: 96%
“…This study illustrated that there was an increase in the level of serum apelin in the sepsis group compared to the non-sepsis group. Gad et al 14 found an 8-fold increase of serum apelin in neonates with sepsis compared to the controls. Apelin is upregulated following sepsis, and plays a protective role in sepsis-induced cardiac impairment.…”
Section: Discussionmentioning
confidence: 96%
“…In our study, we found no significant difference in sex and postnatal age between both groups. According to Gad et al (15) , there was no significant difference in sex between the two groups. But Aderem and Underhill (16) reported that male newborns are four times more likely than females to get sepsis.…”
Section: Discussionmentioning
confidence: 90%
“…W ostatnich latach coraz więcej uwagi poświęca się znaczeniu adipokin w rozwoju płodu i noworodka [8][9][10][11][12][13]. Podkreśla się ich rolę w patogenezie zakażeń u noworodków o różnej dojrzałości ciążowej, zwracając uwagę na wpływ wczesnych zakażeń na stężenia niektórych adipokin w surowicy [14][15][16][17][18].…”
Section: Aktywność Hormonalna Tkanki Tłuszczowejunclassified
“…Stężenie apeliny zwiększa się też istotnie w noworodkowych zakażeniach uogólnionych, zwłaszcza we wczesnych sepsach potwierdzonych wyizolowaniem bakterii z krwi, co koreluje ze wzrostem stężenia białka ostrej fazy i mleczanów, przy czym ciężkość zakażeń nie ma znaczenia dla zwiększenia stężenia apeliny 12 [14].…”
Section: Inne Mechanizmy Działania Apelinyunclassified